1976
DOI: 10.1037/h0077235
|View full text |Cite
|
Sign up to set email alerts
|

Gastric pathology and aphagia following lateral hypothalamic lesions in rats: Effects of preoperative weight reduction.

Abstract: The body weights of male albino rats were reduced gradually to 80% of normal body weight by restricting food intake (dieting), and then the rats were given lateral hypothalamic (LH) lesions. Compared with rats of normal body weight sustaining similar brain lesions, the dieted group displayed a shorter period of postoperative aphagia and less gastric pathology. In a second experiment, a group of rats was reduced to 80% of normal body weight by withholding all food (fasting) and then given LH lesions. Compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
37
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 53 publications
10
37
0
Order By: Relevance
“…This sustained the animals at ϳ400 gm, which is only slightly less than the 450 gm average weight expected for F-344 rats maintained on ad libitum feeding. Although this does not represent a severe degree of caloric restriction, and this restricted feeding schedule did not begin until the rats were 10 months of age, it is well known that animals maintained on restricted feeding schedules have lower mortality rates and increased longevity, and it has been reported that recovery from brain injury is faster and more complete in food-restricted rats (Grijalva et al, 1976;Schallert and Whishaw, 1978;Schallert, 1989), even in aged rats (Joseph et al, 1983), and that food-restricted rats suffer fewer complications (Grijalva et al, 1976;Luszawska et al, 1977). Therefore, it is possible that the acceptably low mortality rates seen in the present study may be partly attributable to the use of fairly long-term scheduled feedings.…”
Section: Discussionmentioning
confidence: 99%
“…This sustained the animals at ϳ400 gm, which is only slightly less than the 450 gm average weight expected for F-344 rats maintained on ad libitum feeding. Although this does not represent a severe degree of caloric restriction, and this restricted feeding schedule did not begin until the rats were 10 months of age, it is well known that animals maintained on restricted feeding schedules have lower mortality rates and increased longevity, and it has been reported that recovery from brain injury is faster and more complete in food-restricted rats (Grijalva et al, 1976;Schallert and Whishaw, 1978;Schallert, 1989), even in aged rats (Joseph et al, 1983), and that food-restricted rats suffer fewer complications (Grijalva et al, 1976;Luszawska et al, 1977). Therefore, it is possible that the acceptably low mortality rates seen in the present study may be partly attributable to the use of fairly long-term scheduled feedings.…”
Section: Discussionmentioning
confidence: 99%
“…If the cortex is removed 10 days before the LH lesion, there appears to be no protective effect (Glick & Greenstein, 1972a). In this regard, note again that abruptly reducing the body weight of rats over aperiod of a few days before LH lesioning does not prOOuce the protective effect (Grijalva et al, 1976).…”
Section: Lateral Hypothalamusmentioning
confidence: 92%
“…When rats are preoperatively dieted, with their body weights abruptly reduced by the elimination of au access to food for 6 days, there is no protective effect (Grijalva et al, 1976). But body-weight set point should be altered, and yet there is no recovery.…”
Section: Lateral Hypothalamusmentioning
confidence: 99%
“…At no time during the study did ND-Q rats display reductions below 97% of their initial weight. In addition, it should be noted that care was taken to guarantee gradual fasting of PD-Q subjects down to the target percentage (Grijalva, Lindholm, Schallert, & Bicknell, 1976).…”
Section: Methodsmentioning
confidence: 99%